Internalisasi Keberagaman Budaya dengan Pendidikan Karakter di Sekolah Dasar - Hanny Nur Alifia; Dhias Salma; Muh. Husen Arifin; Tuti Istianti (Jurnal Gentala Pendidikan Dasar, 2021)
This article contains the impact of material on diversity in Indonesia with character education in elementary schools. As a teacher, you can internalize learning about diversity in Indonesia with character education which is very important for students. Character education is needed in the 21st century for the moral improvement of the future generation of the Indonesian nation starting from the elementary school level. Character education is needed by students for a moral and ethical generation. Character education is also needed in social life in the surrounding environment. Therefore, as a teacher, it is necessary to instill character education in schools to be applied to everyday life. Indonesia has a lot of cultural diversity that can be internalized with character education. In line with that in elementary schools there is material about cultural diversity, especially in the subject of Social Sciences. The purpose of writing this article is to discuss the role of cultural diversity in character education of students. The analytical method used in this article is a literature study that links the impact of cultural diversity with character education. The material on cultural diversity in Indonesia has an influence on character building in students in elementary schools.